Between Efficiency and Balance: An economics-based perspective on town and country: the example of Switzerland - Thierstein, Alain; Scherer, Roland (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
Regional policy in Switzerland is in the throes of upheaval. Within the context of regional development policy, this article attempts to outline the arguments in favour of the strict allocation perspective in respect of scarce resources. However, empirical reality tells a different story. Fiscal federalism is not able to deploy its full argument because of the existence of various spatial externalities; this provides justification for politics to provide redistribution measures to assist disadvantaged regions. However, redistribution should be organised efficiently. The multitude of interdependencies and spillovers between urban and rural spaces makes it almost impossible to make a clear-cut distinction in cost-benefit terms between favoured and disadvantaged areas and regions.
Keywords: Article